Fashion Portfolio: design and presentation - Kiper, Anna (UK Batsford, 2014)
The book takes the reader through all the major steps of fashion portfolio creation. It features the main components of the design process from the identification of inspiration sources and fashion trends research to conceptualization of a complete fashion collection. The topics covered include mood/fabric boards development, creation of original and innovative textiles as well as fashion silhouettes and garment details development through extensive research, quick design sketching, fabric manipulation, and draping experimentation. Great original designs and illustrations by the author as well as design sketch samples by established designers are provided throughout. There are samples of sketchbooks from professional and emerging fashion artists. The book provides some insight from established fashion and accessories designers on the highlights and challenges of the creative process. It is a great professional reference for techniques in the portfolio development. A beautiful but practical book that provides useful techniques and helps the reader get inside the mind of the designer.
Age Group: Adult
Keywords: Fashion; Art; (FSD213) Advanced Fashion Illustration and Portfolio